(untitled) (Серія: Історія. Політологія, 2025)
Стаття присвячена аналізу концепту «денацифікації» як ключового наративу російської пропаганди у гібридній війні проти України. Досліджено історичне походження терміну, що виник після Другої світової війни та передбачав очищення німецького суспільства від нацистської ідеології, та його спотворене використання в сучасній російській інформаційній сфері. Показано, як російська пропаганда трансформувала концепт «денацифікація» у засіб легітимізації збройної агресії, формування образу зовнішнього ворога та виправдання насильницького втручання у внутрішні справи України. Проаналізовано роль цього наративу у мобілізації російського суспільства, вплив на окуповані території, поширення через медіа та дипломатичні канали, а також його взаємозв’язок з іншими пропагандистськими концептами, зокрема «русофобією» та «деукраїнізацією». Розглянуто підходи до розуміння «денацифікації» основними ідеологами та розробниками цього концепту. This article investigates the concept of «denazification» as a central narrative of Russian propaganda in the hybrid war against Ukraine, focusing on its historical origins, evolution, and strategic use in both domestic and international informational contexts. Originally emerging after World War II, «denazification» referred to a comprehensive set of measures aimed at eliminating Nazi ideology and influence from German society, including legal, cultural, educational, and political interventions. In contemporary Russian discourse, however, the term has been deliberately reinterpreted and instrumentalized as a tool to justify military aggression against Ukraine and to construct an image of Ukraine as an externally threatening, ideologically «tainted» state. The article traces the formation and consolidation of this narrative, highlighting how Russian propaganda employed the label «Nazi» against participants in Ukraine’s Revolution of Dignity and patriotic movements as early as 2014. Following the full-scale invasion of Ukraine in 2022, the concept of «denazification» was amplified and synchronized across federal television channels, social media, and official diplomatic platforms, creating a unified narrative that portrays Russia as a defender of justice and Ukraine as a pro-Nazi, corrupt state. The roles of key ideologues such as A. Gasparyan, T. Sergeyev, and A. Dugin are examined, showing how theoretical and practical justifications for «denazification» were elaborated to support both domestic mobilization and international persuasion. The study emphasizes the mechanisms of dissemination and the narrative’s impact on various audiences, including Russian citizens, residents of Crimea, and populations in the occupied «LPR/DPR» territories, where «denazification» is presented as a protective intervention against a fabricated «Nazi regime». It also examines how the narrative combines historical references to World War II with contemporary political events, reinforcing the perception of Ukraine as inherently ideologically corrupt and legitimizing the extension of Russian influence over its territory. Television, digital media, and diplomatic channels are shown to play critical roles in reinforcing the narrative, creating the illusion of consensus, and suppressing alternative perspectives. Furthermore, the article analyzes the international dimension of the narrative, exploring how it is used to discredit Ukraine and its allies, justify violations of sovereignty and territorial integrity, and legitimize coercive or punitive measures against Ukrainian political actors. By simultaneously targeting domestic and foreign audiences, the concept of «denazification» functions as a strategic instrument of hybrid warfare, combining ideological, informational, and political elements to advance Russia’s objectives. The research concludes that the narrative of «denazification» is a deliberately constructed element of Russian propaganda, designed to legitimize aggression, create the perception of an external enemy, and distort historical memory. It highlights the necessity of understanding this concept as both an instrument of domestic mobilization and a tool of international information influence. Future research should focus on assessing the narrative’s impact on public opinion in Russia and occupied territories, evaluating the effectiveness of countering disinformation strategies, and conducting comparative analyses with other propaganda narratives employed in hybrid conflicts.